2014
DOI: 10.1073/pnas.1404656111
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell analyses of transcriptional heterogeneity during drug tolerance transition in cancer cells by RNA sequencing

Abstract: The acute cellular response to stress generates a subpopulation of reversibly stress-tolerant cells under conditions that are lethal to the majority of the population. Stress tolerance is attributed to heterogeneity of gene expression within the population to ensure survival of a minority. We performed whole transcriptome sequencing analyses of metastatic human breast cancer cells subjected to the chemotherapeutic agent paclitaxel at the single-cell and population levels. Here we show that specific transcripti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
155
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 171 publications
(159 citation statements)
references
References 59 publications
4
155
0
Order By: Relevance
“…In this study, we confirmed that TSA alone could induce DNA damage in ECSS cell lines by detecting of γH2AX and single-cell gel electrophoresis (Fig. 1) When cells encounter environmental stresses, the cellular transcriptional profiles will be altered to adapt and overcome the stresses [35]. The stress-responsive genes benefit the cell for better survival.…”
Section: Discussionsupporting
confidence: 67%
“…In this study, we confirmed that TSA alone could induce DNA damage in ECSS cell lines by detecting of γH2AX and single-cell gel electrophoresis (Fig. 1) When cells encounter environmental stresses, the cellular transcriptional profiles will be altered to adapt and overcome the stresses [35]. The stress-responsive genes benefit the cell for better survival.…”
Section: Discussionsupporting
confidence: 67%
“…4 In addition to basic functional studies of healthy tissue, single cell transcriptomics also makes it possible to study the states of diseased cells both before and after drug treatment, and has been employed to profile mutations that drive drug resistance in tumors. 5 We recently introduced a photochemical method for more precisely isolating mRNA from single cells within living tissue using Transcriptome In Vivo Analysis (TIVA). 6 …”
Section: Introductionmentioning
confidence: 99%
“…Genetic mutations and functional changes at the proteomic level alter the cellular composition and thus might change inherent density signatures. Further biological changes during many physiological events, such as differentiation (1,2), cell death (3,4), aging (5), immune response (6, 7), or drug resistance (8) are accompanied by transient changes in cellular magnetic signatures, predominantly owing to the formation of intracellular paramagnetic reactive oxygen species. Characterizing these dramatic changes in fundamental cellular properties down to the individual cell level can reveal subpopulations in seemingly homogenous populations that cannot be seen using conventional assays, which average out or dilute changes in these cellular subsets (9).…”
mentioning
confidence: 99%